0778 Maternal Anxiety and its Association with Perceptions of Infant Sleep-Related Behaviours. (12th April 2019) - Burdayron, Rebecca; Laganière, Christine; Butler, Bryan; Dubois-Comtois, Karine; Béliveau, Marie-Julie; Pennestri, Marie-Hélène
Abstract: Introduction: Perinatal studies have shown a robust association between increased maternal sleep deprivation and increased maternal depressive symptoms. However, studies examining the link between maternal anxiety and sleep in new mothers are scarce and have yielded mixed results. One recent study found that anxious mothers were more likely to misinterpret their infant's crying and feeding behaviours. Therefore, the aim of this study is to examine the associations between maternal anxiety and perceptions of infant sleep-related behaviours. Methods: Mothers (n = 38) at 6 months post-partum completed the State-Trait Anxiety Inventory (STAI) and the Sleep Practices Questionnaire (SPQ). SPQ items were used to determine the degree to which mothers perceived their infant's sleep-related behaviours as problematic (1: not at all to 5: definitely). Items included: 1) "How much of a problem for you are your baby's night wakings?", 2) "Overall, how much of a problem is it for you to put your baby to sleep at bedtime?", 3) "How much of a problem for you is it to help your baby learn to sleep through the night?", and 4) "How much of a problem for your baby is it to learn to sleep through the night?". Pearson correlations were used to assess the relations between maternal anxiety and maternal perceptions. Results: Mothers with higher levels of anxiety reported that their infant's nocturnal awakenings were more problematic (r=0.43; p<0.01). They also reported that it was more problematic for them to put their infant to sleep at bedtime (r=0.41; p <0.05), for them to help their infant learn how to sleep through the night (r=0.40; p<0.05), and for their infant to learn how to sleep through the night (r=0.45; p<.01). Conclusion: Findings add to the existing perinatal sleep literature by considering mothers' perceptions of their infants' sleep-related behaviours in addition to their anxiety. Present results suggest that maternal anxiety is related to the degree to which mothers perceive their infant's sleep behaviours as problematic. Maternal perceptions should therefore be considered by clinicians when working with new mothers. Support (If Any): SSHRC, FRQS